ANALISIS MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN BANGUN RUANG KELAS VI MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Hajar, Dwi Fatmi; Ramadianti, Winda (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
The knowledge that is always being developed is knowledge about mathematics. Mathematics is a science that can train a person's thinking and logical abilities. Apart from that, research also focuses on other research in everyday life, especially the science of problem solving. Mathematics education is about connecting, designing, and creative learning. Sometimes studying mathematics in class can feel scary compared to other subjects, especially when it involves shapes. Abstract shapes have three-dimensional geometric concepts such as cubes, blocks, pyramids, prisms, cylinders and balls which are not easily understood with explanations or two-dimensional drawings. To overcome this problem, teachers should use teaching methods that increase students' conceptual understanding and make learning problem-based (PBL). The subject of this research is class VI of SD IT Uswatun Hasanah Padang Jaya. There are 29 students. The results of the research showed that 82.86% of students felt happy, so it was concluded that the use of PBL in mathematics education made students motivated in learning, especially class VI Bilal SD IT Uswatun Hasanah Padang Jaya.